Hiring woman as leader in an organization a risk?: a case of Malaysian takaful company / Affiaine Ahmad, Zuriah Abdul Rahman - Abdul Rahman, Zuriah (Faculty of Business Management, UiTM Puncak Alam, 2014)
The main purpose of this paper is to examine the relationship of commitment, management, attitude and risk of hiring women as a leader. This empirical study focuses on Malaysian Takaful Companies. The study utilized a survey approach which involved 150 respondents. The sample for this study was drawn from urban population in Klang Valley. Findings showed that all factors have no significant relationship with the hiring of women. Future studies could include other factors such as cultural, economic circumstances, learning, media and information system as independent variables. The study has provided a basis understanding on women credibility of Malaysian Takaful companies. The findings of this paper also have several implications, which would undoubtedly benefits the Takaful companies to bring innovation management into the organization while at the same time making them to realize the equal potential of workers in Malaysian Takaful companies.